PROMOSI PENJUALAN MELALUI JEJARING SOSIAL (Studi Deskriptif KualitaIif Promosi Penjualan melalui Jejaring Sosial Instagram pada “PT JHD RANDOL”) - Christopher Yudha Erlangga (Jurnal Komunikasi, 2017)
This research entitled Sales Promotion through Social Networking (Qualitative Descriptive Study of Sales Promotion through Instagram Social Networking on "PT JHD RANDOL" This research aims to find out the promotion through Instagram @radjacendol account by PT JHD RANDOL The theory used and considered relevant In this research is Mass Communication Theory, Social Media (New Media), Interest in Buying and Marketing Promotion.The method used in this study using qualitative methods.The subject of this study is the consumer Radja Cendol who also followed the account Instagram @radjacendol and President Director of PT JHD RANDOL Danu Sofwan Technique The data collecting is done by observation around research subject and in-depth interviews This research found some conclusions, such as @radjacendol Account promoting by disseminating information of new menu, interesting quote, motivation word, current issue of contest with prize And others la In. The interaction with consumers also raises customer loyalty to Radja Cendol. These interactions are also not uncommon to bring in new customers. The existence of this account also makes a difference with other competitive products. Customer interest Radja Cendol influenced by several factors such as the spread of many outlets, affordable prices affordable, as well as nutritious and healthy products. Keywords : Promotion, Buying Interest, Radja Cendol Instagram.